Recent Advances in Gold Nanocluster-Based Biosensing and Therapy: A Review - Lu Yang; Pengqi Hou; Jingyi Wei; Bingxin Li; Aijun Gao; Zhiqin Yuan (Molecules, 2024)
Gold nanoclusters (Au NCs) with bright emission and unique chemical reactivity characters have been widely applied for optical sensing and imaging. With a combination of surface modifications, effective therapeutic treatments of tumors are realized. In this review, we summarize the recently adopted biosensing and therapy events based on Au NCs. Homogeneous and fluorometric biosensing systems toward various targets, including ions, small molecules, reactive oxygen species, biomacromolecules, cancer cells, and bacteria, in vitro and in vivo, are presented by turn-off, turn-on, and ratiometric tactics. The therapy applications are concluded in three aspects: photodynamic therapy, photothermal therapy, and as a drug carrier. The basic mechanisms and performances of these systems are introduced. Finally, this review highlights the challenges and future trend of Au NC-based biosensing and therapy systems.